Measurements of t¯t differential cross-sections of highly boosted top quarks decaying to all-hadronic final states in pp collisions at √s p = 13 TeV using the ATLAS detector - Alconada Verzini, María Josefina (2018)
Measurements are made of differential cross-sections of highly boosted pair-produced top quarks as a function of top-quark and t ̄t system kinematic observables using proton-proton collisions at a center-of- mass energy of ffiffi s p 1⁄4 13 TeV. The data set corresponds to an integrated luminosity of 36.1 fb−1, recorded in 2015 and 2016 with the ATLAS detector at the CERN Large Hadron Collider. Events with two large- radius jets in the final state, one with transverse momentum pT > 500 GeV and a second with pT > 350 GeV, are used for the measurement. The top-quark candidates are separated from the multijet background using jet substructure information and association with a b-tagged jet. The measured spectra are corrected for detector effects to a particle-level fiducial phase space and a parton-level limited phase space, and are compared to several Monte Carlo simulations by means of calculated χ2 values. The cross- section for t ̄t production in the fiducial phase-space region is 292 7ðstatÞ 71ðsystÞ fb, to be compared to the theoretical prediction of 384 36 fb.